1,3,4-thiadiazole derivatives. Synthesis, structure elucidation, and structure-antituberculosis activity relationship investigation - (:unkn) unknown (AMER CHEMICAL SOC, 2004)
A series of 2,5-disubstituted-1,3,4-thiadiazoles were synthesized, the compounds structures were elucidated and screened for the antituberculosis activity against Mycobacterium tuberculosis H37Rv using the BACTEC 460 radiometric system. Among the tested compounds, 2-phenylamino-5-(4-fluorophenyl)-1,3,4-thiadiazole 22 showed the highest inhibitory activity. The relationships between the structures of compounds and their antituberculosis activity were investigated by the Electronic-Topological Method (ETM) and feed forward neural networks (FFNNs) trained with the back-propagation algorithm. As a result of the approach, a system of pharmacophores and anti-pharmacophores has been found that effectively separates compounds of the examination set into groups of active and inactive compounds. The system can be applied to the screening and design of new active compounds possessing skeletons similar to those used in the present study.
Keywords: NEURAL-NETWORK; ANTIMICROBIAL ACTIVITY; SUBSTITUTED 1,3,4-THIADIAZOLES; ANTICONVULSANT ACTIVITY; THIADIAZOLES; HETEROCYCLES; SERIES